Oral Lichen Planus and Polycythemia: Possible Association - Yassine Oueslati; Raouaa Belkacem Chebil; Haifa Regaieg; Lamia Oualha; Nabiha Douki (Hindawi Limited, 2020)
Oral lichen planus is a chronic inflammatory disease of established immune-mediated pathogenesis that affects the oral mucosa. Polycythemia is a nonaggressive myeloproliferative disorder, characterized by an increase in red blood cell mass, often with uncontrolled production of granulocytes and platelets. Their association was rarely mentioned in the scientific literature. The aim of this paper was to report their occurrence in a 52-year-old male patient. Although a casual connection cannot be excluded, both diseases share many similarities in the immune dysfunctions involved in their pathogenesis and their clinical features. Such a hypothesis remains to be demonstrated by further studies. The presence of oral lesions should alert the clinicians in the process of identifying and early diagnosing these diseases. Thus, complications can be prevented and treatment can be started at an early stage, avoiding further damage.